Literature survey : Moisture sportion of nylon - Chua, Jian Wei. (2010)
Moisture Sorption is the penetration and dispersion of water, in either liquid or gas onto or throughout a polymer. Moisture sorption is the most important ability of a polyamide since it can change the working characteristic of the polyamides drastically, such as melting and glass transition points, strength and electrical properties of the polymer. Sorbed water molecules in polyamides are mainly of three types: 1. Interacting with free amide groups; 2. Rupturing the hydrogen bonds between amide groups; and 3. Forming clusters. The sorption of moisture by polyamide is best represented with a modified dual-mode sorption equation. The Langmuir equation calculates the volume fraction of adsorbed water, while the Flory-Huggins equation calculates volume fraction of water absorbed. The model incorporates the works of Zimm and Lundberg and predicts clustering of the sorbant. Three main approaches towards predicting moisture sorption had been taken. In the group contribution method, calculation of moisture sorption is made with the cumulative number of water molecules of each functional group on the polymer structure. The empirical approach analyses experimental data to establish an empirical correlation between the amount of sorbed water and the parameter of solubility. The last approach uses the Flory-Huggins theory, incorporating the Langmuir equation and cluster formation. The results may be used in the study of the hydrolytic stability of polyamides and predicting the sorption capability of new polyamides synthesized in future without conducting actual experiments.